Electronic regulation of a core–shell NiSe2 catalyst by Co doping to accelerate hydrogen evolution. Issue 45 (3rd November 2022) - Xu, Huakai; Lu, Kebin; Jiang, Chuanhai; Wei, Xiaofei; Wang, Zhifei; Ouyang, Yuguo; Dai, Fangna
Abstract : A Co-doping core–shell shaped NiSe2 based catalyst (Ni x Co1− x Se2 @NC) exhibits promising electrocatalytic activity for HER with a low overpotential of −143 mV at −10 mA cm −2, a small Tafel slope of 37.5 mV dec −1 . Abstract : As a narrow bandgap semiconductor, transition metal selenides are promising as excellent electrocatalysts for hydrogen evolution reactions (HERs). Herein, using an ultra-thin MOF as the precursor, a Co-doped core–shell shaped NiSe2 based catalyst is successfully constructed by a two-step calcination method as an efficient HER catalyst. Experiments and theoretical calculations indicate that the introduction of Co adjusts the electronic structure of Ni and Se, promoting charge transfer and reducing the energy barrier of the rate-limiting step to accelerate the hydrogen precipitation reaction. In addition, the core–shell structure contributes to mass transport, and the outer carbon layer improves the stability of the catalyst. The optimal catalyst (Ni0.75 Co0.25 Se2 @NC) exhibited satisfactory electrocatalytic activity as evidenced by a low overpotential of −143 mV at a current density of −10 mA cm −2 and a small Tafel slope of 37.5 mV dec −1 . This work provides a valuable strategy for fabricating efficient NiSe2 based electrocatalysts for the HER.